Repuesta de la gallinaza como suplemento alimenticio en bovinos de carne, hacienda la Providencia, parroquia San José del Tambo, provincia Bolívar - Rumiguano Quilligana, William Robinson (2015)
The exploitation and livestock production around the world is of vital importance for your contribution to food security. In the Bolivar province, particularly in the subtropics, it is regarded as an essentially pastoral activity, depending fundamentally on the contribution of nutrients from the fodder, and the improvement of the productive and reproductive indicators of cattle that originates. This research was conducted in the agroecological zone of San José del Tambo. The objectives were: i) To evaluate the response of four levels of manure on the weight gain in bovines. ii) To determine palatability of feed conversion in cattle manure, up to 120 days. (iii) Economic analysis of partial budget (APP). Four treatments that constituted the percentages of man ure (0%, 15%, 20% and 25%) were with 10 replications. A completely randomized design was applied. Analyses of variance, Tukey test at 5%, economic partial budget analysis and proximal nutritional analysis of food block, chicken manure and pasture Braquiaria. The main variables that were measured were initial weight, increasing weight every 15 days, final weight,total forage consumption and palatability. The most relevant results were: there was a significant positive effect of manure on the increase in wei ght, but it was not economically profitable. The increase of the weight of the vaconas was mainly related with the age, the time (months), nutrition and animal health. Finely this research, showed that it is not economical to add in the nutritional supplement the chicken manure, most important being the best livestock practices related to nutrition and health, which contributes to Animal welfare.